Convenção sobre os direitos das pessoas com deficiência da ONU, seu protocolo facultativo e a acessibilidade - Lopes, Laís Vanessa Carvalho de Figueirêdo (2009)
This study aims at analyzing the new world-view on persons with disabilities and the right to accessibility, established in the legal mark represented by the Convention on the Rights of Persons with Disabilities and its Optional Protocol, passed on December 13, 2006, by means of the Resolution 61/106, during the 61st session in the United Nations General Assembly (UN) as part of a set of international human rights treaties adopted since 1948. To that effect, it will develop its legal rationale aiming at answering the following questions: 1. History: What are the historical context and the main views on disability that have prevailed in the course of humankind s history in the construction of the human rights of persons with disabilities from a legal standpoint, in the international sphere? 2. Procedures: How has the procedure of preparation of the Convention on the Rights of Persons with Disabilities and its Optional Protocol developed in UN? And the one for the ratification with constitutional equivalence in Brazil of the first treaty of human rights in the 21st century after Constitutional Amendment nº 45/04? What are the mechanisms of domestic and international monitoring of the implementation of the legal tools in caption? 3. Rights: Who are the persons with disabilities benefiting from the Convention on the Rights of Persons with Disabilities and its Optional Protocol? What are the main rights and principles contained in the UN documents? 4. Accessibility: What is accessibility and what is its legal nature? How can one ensure the enforcement of accessibility amidst the other human rights?